Aplikasi Model Pembelajaran Inquiry Sebagai Upaya untuk Meningkatkan Prestasi Belajar Matematika - Suhendrayani, Ketut (Universitas Pendidikan Ganesha, 2018)
The learning process in the classroom that makes low student achievement is the basis for making this classroom action research. This research was carried out in class VIII A5 at SMP Negeri 3 Sawan in even semester of 2017/2018 school year. Research data were collected using tests and analyzed using descriptive analysis. After all the processes were carried out which began with planning, continued with the implementation continued with observation/data collection and ended with a reflection that was doing analysis, it turned out that the data obtained was quite encouraging. The initial value which was initially low was 69.23 with learning completeness only at 7.69%, and in the first cycle, it had increased to 79.04 with 65.38% learning completeness and significantly increased in Cycle II to 83.65 92.31% learning completeness. This data shows the success of this class action research so that the researcher concludes that the Inquiry learning model can improve the mathematics learning achievement of VIIIA5 students in SMP Negeri 3 Sawan.